พระสงฆ์ในกระแสของโลกยุคใหม่: พฤติกรรมอันเป็นที่ถกเถียงและบทบาท ที่เปลี่ยนแปลงในศตวรรษที่ 21 - (อุธ จันทุม), พระครูสุธีวรสาร; เสนามาตย์, ชนันท์ธิพัฒน์; พุทธา, สุรศักดิ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2024)
This article aims to analyze the roles and behaviors of Thai Buddhist monks in the rapidly evolving context of the modern global society. It focuses on examining the changing roles, duties, and lifestyles of monks as they navigate challenges posed by modern technology, digital communication, and diverse public expectations of religious institutions in the 21st century. Key issues explored include the use of social media, public expression, and participation in social activities that may conflict with traditional Buddhist monastic codes. This in-depth analysis seeks to understand factors influencing monks’ adaptation to contemporary society, as well as the impact of these changes on the public perception of the monastic institution in Thailand. Additionally, the article investigates the evolving role of monks as spiritual leaders and religious teachers, examining how they must adapt to a modern society driven by globalization, consumerism, and the younger generation's desire for individuality. Emphasis is placed on the necessity for monks to maintain a balance between adapting to contemporary life and upholding the traditional values of Buddhism. The study also assesses the challenges these shifts may pose to the credibility and spiritual authority of monks in the future. Finally, this article presents policy-oriented recommendations and suggestions for enhancing the role of monks in the 21 st century to align with the lifestyles of modern society while preserving the sanctity and enduring values of Buddhism.